2017
DOI: 10.3389/feart.2017.00014
|View full text |Cite
|
Sign up to set email alerts
|

Sub-seasonal Predictability of the Onset and Demise of the Rainy Season over Monsoonal Regions

Abstract: Sub-seasonal to seasonal (S2S) retrospective forecasts from three global coupled models are used to evaluate the predictability of the onset and demise dates of the rainy season over monsoonal regions. The onset and demise dates of the rainy season are defined using only precipitation data. The forecasts of the onset and demise dates of the rainy season are based on a hybrid methodology that combines observations and simulations. Although skillful model precipitation predictions remain challenging in many regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
19

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 51 publications
2
62
0
19
Order By: Relevance
“…Our results pertain to the entire calendar year and predictability may be higher in specific parts of the calendar year, and especially during the early and late phases of the monsoon seasons including the onset and/or demise dates. 57,58 Over the oceans, the skill is larger and the contribution of the S2S climate drivers is stronger than over land. The predictability types are organized broadly in a symmetric way, around the tropical Indian and Pacific Ocean where the skill/scale peak.…”
Section: Discussionmentioning
confidence: 99%
“…Our results pertain to the entire calendar year and predictability may be higher in specific parts of the calendar year, and especially during the early and late phases of the monsoon seasons including the onset and/or demise dates. 57,58 Over the oceans, the skill is larger and the contribution of the S2S climate drivers is stronger than over land. The predictability types are organized broadly in a symmetric way, around the tropical Indian and Pacific Ocean where the skill/scale peak.…”
Section: Discussionmentioning
confidence: 99%
“…Regions adjacent to the ocean display higher skill suggesting a possible role for the ocean with regards to regional predictability. Recently, Bombardi et al (2017) found that subseasonal forecasts generally outperform climatology when predicting the onset date of the monsoon, and for the AM, Moron et al (2017) found a drop in the spatial coherence of interannual variations of subseasonal to seasonal FIGURE 12 | Mean MME Week 3-4 RPSS averaged over continental monsoon regions for observed phases of Niño3.4 index (A) and MJO phases (B) measured by the RMM1 and RMM2 indices of Wheeler and Hendon (2004). Black, gray, and light gray lines correspond to the 90% level of significance over the respective North American, West African and Asian summer monsoon regions using Monte Carlo simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of monsoons and monsoon rainfall remains a challenge for state‐of‐art climate models (e.g., Becker et al ., ). However, there is evidence that timing of monsoons can be predicted on lead‐times of weeks to months (Vellinga et al ., ; Alessandri et al ., ; Bombardi et al ., ; Chevuturi et al ., ). In this section we discuss the predictability of the timing of monsoons in dynamical models, including the representation of the timing of monsoons in global climate models.…”
Section: Predictability Of Monsoon Onset and Ending Datesmentioning
confidence: 99%
“…To ensure consistent calculation of the timing of the rainy season across the globe, Bombardi et al . () start the calculation from the minimum of the first harmonic of the mean annual cycle of rainfall, while Diaconescu et al . () and Dunning et al .…”
Section: Defining Onset and End Datesmentioning
confidence: 99%